Pengaruh Konsumsi Listrik dan Industrialisasi terhadap Pertumbuhan Ekonomi - Buhaerah, Pihri (Jurnal Ekonomi dan Pembangunan, 2018)
AbstractThe structure of GDP nowadays is still dominated by households. As a result, economic growth stands at 5 percent. To boost economic growth performance, industrialization should be taken into account. In the process, energy availability particularly electricity becomes one of the main components. For this reason, the main purpose of this study is to measure the effect of electricity and industrialization on economic growth. To do so, this study employs ARDL model and uses secondary data with sample period from 1987 to 2016. Regression result analysis shows that electricity consumption, manufacturing, workers in the industrial sector, household consumption, and trading volume empirically significant both in the short-run and long-run. Interestingly, the value of the electricity consumption coefficient, the added value of processing industries, and the proportion of workers in the industrial sector are positive indicating that those variables contribute positively to economic growth. Meanwhile, the value of household consumption coefficient and trading volume is negative. This indicates that those variables contribute negatively to economic growth. Interestingly, among the five explanatory variables, electricity consumption is the strongest variable in boosting economic growth both in the short-run and the long-run. In addition, bounds cointegration test shows that all explanatory variables involved in this study have a long-term relationship with economic growth.